Cost-effectiveness analysis of mectizan treatment programme for onchocerciasis control: operational experiences in two district of Southern Nigeria (2009)
Objectives: This study analyze the operational costs of two Mectizan treatment strategies in relation to their effectiveness. Methods: The study was conducted in 24 communities located in Irewole and Egbeda districts of Osun and Oyo State, Nigeria respectively. Cost-effectiveness analysis included retrospective analysis of cost of treatment, review of records of distributors, estimation of overall cost-effectiveness ratio of treatment and distribution, calculation of mean cost-effectiveness ratios and statistical comparison of the mean cost-effectiveness ratios. Results: Overall cost of treatment per person through mobile distribution was N27.39 (USD1.16) while the corresponding overall cost through community-directed distribution was N14.35 (USD0.61). Overall cost of distribution per tablet through mobile distribution was N20.97 (USD0.89) while the corresponding overall cost through community-directed distribution was N8.39 (USD0.36). The difference between the mean cost-effectiveness ratios for treatments through mobile distribution, 56.79, and community directed distribution, 32,53, was not statistically significant (p=0.120265). Similarly, the difference between the mean cost-effectiveness ratios for distribution of tablets through mobile distribution, 40.83, and community-directed distribution, 19.17, was not statistically significant (p=0.167249). Treatment coverages were 59% and 80%, and 2,376 and 4,148 tablets were respectlveIy distributed, Conclusion: Distribution of Mectizan tablets by community-directed distributors was more cost-effective than by mobile health staff, but the differences in cost ere not statistically significant. However, this could ensure self-reIiance and sustainability of treatment programmes, which are prerequisites for decision making on treatment strategies.